Outcomes benefit in asymptomatic patients with moderate aortic valve stenosis followed up in heart valve clinics. (3rd October 2022) - Paolisso, P; Mileva, N; Gallinoro, E; Beles, M; De Colle, C; Bertolone, D T; Spapen, J; Brouwers, S; Penicka, M; Van Camp, G
Abstract: Background: The management of patients with asymptomatic moderate aortic stenosis (AS), particularly the follow-up and the choice between early intervention vs watchful waiting, remains debated. A progressively increasing number of patients with valvular heart disease (VHD) were diagnosed and followed in an ambulatory setting with a dedicated cardiologist and cardiac imaging specialist: the Heart Valve Clinics (HVC). However, the number of patients with VHD is that high, that these patients are also followed by routine cardiac care consultations (standard-of-care). Purpose: To determine the benefit of a HVC approach and outcomes compared to standard-of-care for patients with moderate asymptomatic AS. Methods: From November 2014 a HVC environment was introduced at our Cardiovascular Center, to follow patients with moderate and severe VHD by an imaging and valve specialist. Patients who received at least one visit in the Ambulatory HVC were included in a prospective registry. All consecutive patients with aortic valve velocity max>3 cm/sec diagnosed with 2-D echocardiography according to the ESC Guidelines were included in this study. Exclusion criteria included more than moderate aortic regurgitation and prior aortic valve replacement (AVR). Natural history, need for AVR, and survival of patients with baseline moderate AS were assessed at follow up. Cox proportional hazard model, Kaplan-Meier survival curves and propensity score matching where used to assess the HVC approach effect on the mortality. Results: A total of 2130 patients were included (1879 in the standard-of-care group and 251 in the Ambulatory HVC group). 1187 (55.7%) were male, and the mean (SD) age was 77.2±12.2 years. A total of 919 patients (43.1%) had severe AS (aortic valve area <1.0 cm 2 ). Mean clinical follow-up was 1.2±2.4 years. A total of 822 patients (38.6%) died during the follow up and 114 patients (55.6%) underwent AVR during the study period. After using 1:1, nearest neighbour, without replacement propensity score matching, baseline characteristics between the two groups were balanced. The introduction of Ambulatory HVC was associated with a reduction of adjusted all-cause mortality compared to the standard-of-care group (HR=0.53, 95% CI 0.35–0.82, p=0.004) (Figure1). At multivariable analysis, the Ambulatory HVC pathway was a significant predictor of reduced all-cause of death (HR=0.46, 95% CI 0.33–0.65, p<0.001), together with younger age and higher GFR, independently of AVA, tricuspid regurgitation gradient, LVEF and chronic obstructive pulmonary disease. Conclusions: Patients with moderate AS followed up in HVC had lower rate of all-cause of death compared to the standard-of-care group. The Ambulatory HVC was a significant predictor of reduced all-cause of death and was associated with more efficient patient management and lower mortality. Dedicated HVC have the potential to improve patient care and clinical outcomes. Funding Acknowledgement: Type of funding sources: None.